2006
DOI: 10.1080/16501970600680262
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Training Compared With Resistance Training: Effect on Spasticity, Muscle Strength and Motor Performance in Adults With Cerebral Palsy

Abstract: These data suggest that an 8-week intervention of whole-body vibration training or resistance training can increase muscle strength, without negative effect on spasticity, in adults with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
176
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(197 citation statements)
references
References 26 publications
13
176
0
8
Order By: Relevance
“…The first study used an unconventional method of whole-body vibration (WBV) in static standing with the intervention group, and the control group participated in resistance training. 17 This study did not demonstrate statistically significant within-group differences when comparing resistance training with WBV (ps ¼ 0.50 and 0.72, respectively). Despite the lack of statistically significant differences, the authors of this study reported that they found clinically significant decreasing spasticity in knee extensors in the WBV group as well as an improvement in the participants' gross motor function.…”
Section: Quality Assessmentmentioning
confidence: 89%
See 3 more Smart Citations
“…The first study used an unconventional method of whole-body vibration (WBV) in static standing with the intervention group, and the control group participated in resistance training. 17 This study did not demonstrate statistically significant within-group differences when comparing resistance training with WBV (ps ¼ 0.50 and 0.72, respectively). Despite the lack of statistically significant differences, the authors of this study reported that they found clinically significant decreasing spasticity in knee extensors in the WBV group as well as an improvement in the participants' gross motor function.…”
Section: Quality Assessmentmentioning
confidence: 89%
“…18 Three of the studies used participants who were young adults (aged 18-27 y, SD ¼ 2.5), 11,14,15 and three studies used participants ranging from their early 20s to their late 50s. [16][17][18] Participants in two studies had spastic diplegia; 11,17 in one, they had spastic tetraplegia; 14,18 in another, they had bilateral spasticity. 15 Two studies included participants with various types of spasticity.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that PD may produce a general impairment of proprioceptive guidance and that muscle vibration could be a tool for improving sensorimotor processing. Whole body vibration (WBV) has been demonstrated to be a possible tool to improve balance by enhancing sensorimotor processing in both elderly subjects (Bruyere et al, 2005) and patients with neurological impairment (cerebral palsy, Multiple Sclerosis and stroke) (Ahlborg et al, 2006;Schuhfried et al, 2005;Van Nes et al, 2006). Bruyere et al investigated the effectiveness of WBV intervention in improving gait and balance in a group of forty-two elderly volunteers by means of the Tinetti test, Time Up&Go and the health related QoL (SF-36) (Bruyere et al, 2005).…”
Section: Sensorimotor Integration Trainingmentioning
confidence: 99%